UJI BAKTERIOLOGIS PADA AIR SUMUR WARGA DI KELURAHAN BATUANG TABA NAN XX KECAMATAN LUBUK BEGALUNG KOTA PADANG - Kurniawati, Rina Afrida; Indriati, Gustina; Wati, Meliya (Pendidikan Biologi, 2013)
ABSTRAK Well water used residents to still questionable quality as the distanced between saptic tanks, livestock barns, wells river with less than 10 maters and the well being around the environment that a lot of junk. Well water is very susceptible to bacterial contamination and an bacterial contamination and an issue that needs attention because residents use well water as a source of drinking water. Bacterial contamination can cause various diseases, one if which diare. According   to   the   Keputusan   Menteri   Kesehatan   (KepMenKes)   RI   No.492/Menkes/PER/IV/2010 about drinking water quality requirements have value MPN E. coli sel/100 mL. This study aims to determine the water quality of wells in  Kelurahan  Batuang Taba Nan  XX Kecamatan  Lubuk  Begalung of Padang States  from  the  aspects  of  baketriologis.  This  study  conducted  from  July  to August 2013 held the Laboratory of Basic Biology STKIP PGRI West Sumatera. This research is descriptive study sampling is Proposive Sampling of 8 wells based on the distance of less than 10 maters of pollution sources. This study uses the   Most   Probable   Number   (NPM)   using   two-stage   trial   the   prediction (Presumtive Test) and test or certainty (Confirmative Test) with a combination of3:3:3. Based on the research conducted showed that the well water contaminatedwith Escherichia coli positive citizens with amounts ranging from 1100 to >2400 sel/100 mL, the water category, including poor water quality, does not meet clean water standards and is not suitable for consumption as drinking water.